Geographic Information System of Dental Caries Management (SIG-MKG) to Improve The Quality Of Information In Dental And Oral Health Services In Puskesmas - Luci Fitriyanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
ABSTRACTThe program to reduce the development of dental caries in elementary school children has not been optimal. So far, the reporting mechanism of the inspection results is still manual so that the resulting data is inaccurate and incomplete. The dental caries management geographic information system (SIG-MKG) provides dental caries distribution data in support of effective and targeted handling. The purpose of this research is to produce a decent SIG-MKG and its application effectively improve the behavior of dental and oral therapists and the quality of data and information. The methods used are Research and Development and pre-experimental design method. Respondents numbered 30 to assess the behavior (knowledge, attitude, and action) of Dental and Oral Therapists in the application of SIG-MKG and the quality of data and information. Expert validation test on SIG-MKG obtained an average feasibility of 97.23%. Assessment of knowledge, attitudes, and actions after treatment increased significantly compared to before (p=0.001, p=0.032, and p=0.001, respectively). Quality of data and information improved significantly after treatment (p=0.001). Behavior affects Dental Caries Management Quality and Quality of data and information (p=0.001).It can be concluded that SIG-MKG provides a significant improvement in the behavior of Dental and Oral Therapists in the application of SIG-MKG and the quality of data and information compared to before.Keywords: Dental Caries Management; Geographic Information Systems.